The tormented alliance : American servicemen and the occupation of China, 1941-1949 - Fredman, Zach (The University of North Carolina Press, 2022)
"A military alliance with the United States means a military occupation by the United States. That is the truth Zach Fredman uncovers in The Tormented Alliance. The first book to draw on archives from all of the areas in China where U.S. forces deployed during the 1940s, it examines the formation, evolution, and undoing of the alliance between the United States and the Republic of China during World War II and the Chinese Civil War"--